Efficacy and Safety of Tranexamic Acid Versus ϵ-Aminocaproic Acid in Cardiovascular Surgery. (December 2014) - Falana, Olabisi; Patel, Gourang
Background: Blood conservation is a major concern in the management of surgical patients because of transfusion-related complications, limited supply, and health care costs. Tranexamic acid (TXA) and ϵ-aminocaproic acid (ϵACA) are lysine analogue antifibrinolytics used to reduce surgical bleeding and transfusions.Objective: To evaluate the efficacy and safety of TXA compared with ϵACA in the management of cardiovascular surgical bleeding at an academic medical center.Methods: This single-center, retrospective, observational cohort study included 120 patients undergoing cardiovascular surgery with or without cardiopulmonary bypass, who received at least 1 dose of perioperative TXA or ϵACA. The efficacy outcome—massive perioperative bleeding—was a composite end point of chest tube drainage >1500 mL in any 8-hour period after surgery, perioperative transfusion of 10 or more units of packed red blood cells, reoperation for bleeding, or death from hemorrhage within 30 days. The safety outcomes were incidence of thromboembolic events, postoperative renal dysfunction, seizure, and 30-day all-cause mortality.Results: The primary end point—massive perioperative bleeding—occurred in 10 patients (16.7%) in the TXA group compared with 5 patients (8.3%) in the ϵACA group ( P = 0.17). There were no significant differences in the secondary end points of 30-day all-cause mortality, thromboembolic events, renal dysfunction, and seizure.Conclusions: There were no differences in the efficacy and safety outcomes between TXA and ϵACA in the management of cardiovascular surgical bleeding at our institution. Considering the substantial cost difference and comparable efficacy and safety, ϵACA may have better value over TXA for reducing cardiovascular surgical bleeding.